Comprehensive nationwide incidence and prevalence trends of atrial fibrillation in Finland - Lehto Mika; Haukka Jari; Aro Aapo; Halminen Olli; Putaala Jukka; Linna Miika; Mustonen Pirjo; Kinnunen Janne; Kouki Elis; Niiranen Jussi; Luojus Alex; Tiili Paula; et al. (BMJ Publishing Group, 2025)
Objective Atrial fibrillation (AF) is a worldwide healthcare challenge owing to population ageing. In this study, we assessed the current trends in the incidence and prevalence of AF for the first time in an unselected, nationwide population.
Methods In the Finnish Anticoagulation in Atrial Fibrillation study, we gathered comprehensive data including all primary, secondary and tertiary healthcare visits and drug reimbursement from national healthcare registers to identify all patients with incident AF between 2004 and 2018 in Finland. Incident AF was defined as new-onset AF occurring after 2007. Time trends for the incidence and prevalence of AF were calculated and stratified by sex and age.
Results A total of 411 387 patients with AF diagnosis were documented in Finland during 2004-2018. In 2018, the incidence and prevalence of AF in the total Finnish population were 469/100 000 and 4.1%, respectively. The incidence of new-onset AF in the adult population (≥20 years) increased from 471/100 000 in 2007 to 604/100 000 in 2018, but the age-adjusted incidence remained stable. The prevalence of AF increased in the adult population from 2.5% to 5.2%, and was higher in men than in women (5.9% vs 4.6%, p < 0.001). The incidence and prevalence of AF increased with age and were 3194/100 000 and 23.4% in patients older than 75 years.
Conclusions Based on comprehensive nationwide data including primary care, we observed an increasing incidence and prevalence of AF over time. This increase was strongly age-dependent with the age-standardised incidence remaining stable during 2007-2018.